Some Coordinated Abilities and Their Relationship to The Accuracy of Performaning the Skill of Serving Among the Koya University Female Volleyball Players (Raparin Journal of Humanities (RJH), 2025)
The research community and sample were chosen deliberately  from the female volleyball players of the Koya University team Academic year (2023-2022), through comprehensive enumeration, which numbered (16) players, and one player was excluded for non-compliance with completing the tests, and (4) were excluded Female players from the university volleyball team because of their participation in the reconnaissance experiment and the extraction of stability, and thus the size of the final sample was (11) players, with a rate of (%68.75) of the research community. The researchers used the descriptive approach, and after obtaining the results, they were discussed in a scientific manner supported by sources to achieve the research objectives. In light of the findings of the two researchers, the followings can be recommended:- Conducting similar studies on other components of the compatibility of abilities with other physical and skillful attributes of female volleyball players- Giving specific percentages of the volume of training to develop the different abilities of the volleyball players- Ensuring the development of tests that include tests for the components of Coordination abilities that contribute to the development of skillful performance and physical attributes of volleyball players- Conducting a similar study on players of different age groups and national teams